Traditional Chinese Medicine Regulating Lymphangiogenesis: A Literature Review - Peng, Longping; Dong, Yidan; Fan, Hua; Cao, Min; Wu, Qiong; Wang, Yi; Zhou, Chang; Li, Shuchun; Zhao, Cheng; Wang, Youhua (Frontiers in Pharmacology, 2020)
Lymphatic vessels, as an important part of the lymphatic system, form a fine vascular system in humans and play an important role in regulating fluid homeostasis, assisting immune surveillance and transporting dietary lipids. Dysfunction of lymphatic vessels can cause many diseases, including cancer, cardiovascular diseases, lymphedema, inflammation, rheumatoid arthritis. Research on lymphangiogenesis has become increasingly important over the last few decades. Nevertheless, the explicit role of regulating lymphangiogenesis in preventing and treating diseases remains unclear owing to the lack of a deeper understanding of the cellular and molecular pathways of the specific and tissue-specific changes in lymphangiopathy. TCM, consisting of compound extracted from TCM, Injections of single TCM and formula, is an important complementary strategy for treating disease in China. Lots of valuable traditional Chinese medicines are used as substitutes or supplements in western countries. As one of the main natural resources, these TCM are widely used in new drug research and development in Asia. Moreover, as a historical and cultural heritage, TCM has been widely applied to clinical research on lymphangiogenesis leveraging new technologies recently. Available studies show that TCM has an explicit effect on the regulation of lymphatic regeneration. This review aims to clarify the function and mechanisms, especially the inhibitory effect of TCM in facilitating and inhibiting lymphatic regeneration.